Gullies in the Northwest of Paraná: preferential occurrence sites in the landscape - de Nóbrega, Maria Teresa; Silveira, Hélio; da Cunha, José Edézio; Beckauser, Maria Carolina; Bonifácio, Cássia Maria [UNESP]; Baldo, e Maria Cleide (My University, 2023)
In the Northwest region of Paraná, in the Southern region of Brazil, the pedological cover is characterized by sandy and medium-textured soils that are highly vulnerable to the installation and development of erosion processes caused by surface water runoff, both concentrated and diffuse. Since the beginning of colonization, erosive processes, particularly gullies, have become alarmingly widespread, and their control and prevention have been constant challenges. Several projects aimed at controlling and rehabilitating areas affected by gullies were not successful, with failures often attributed to insufficient knowledge of the erosion process itself, as well as the organization and dynamics of the environment in which they occur. To contribute to a better understanding of these phenomena in the region, this study presents the results obtained from research conducted in areas affected by gullies. The investigation not only considers the impact of land use and occupation but also explores the preferential geographical situations for gully occurrence in the landscape. Additionally, the study examines the role of relationships between slope forms, the structure and functioning of the pedological cover in morphological and hydric terms, and the influence of intense rainfall on the origin and evolution of erosive forms.
As voçorocas no Noroeste do Paraná: locais preferenciais de ocorrência na paisagem
Keywords: Hollow; Pedological system; Slopes; Water flows